Enhancing Knowledge and Attitude with a Sex Educational Pop-up Book for Adolescents with Intellectual Disabilities - Mansur, Arif Rohman; Sari, Ira Mulya; Deswita, Deswita; Neherta, Meri; Herien, Yelly; Farlina, Mutia; Yuni, Annisa Rahma; Sholihat, Annisa (Journal of Maternal and Child Health, 2023)
Background: Adolescents with Intellectual Disabilities (ID) adolescents lack of understanding, access to information, and limited knowledge of the sexual behaviours of their peers in the general population. The need for accurate information about sex education is very important in order to stay safe and healthy. However, there is no appropriate, population-specific, and empirically validated sexual education content for individuals with intellectual disabilities. Education for Adolescents with ID requires media in concrete or real physical form and is designed in an attractive way so that they can understand the topic or theme being taught, All information about educational objects is displayed in the form of three-dimensional embossed images or commonly called pop-up books. This study aimed to analyze the effectiveness of sex education using the Pop-up Book on the knowledge and attitude of an adolescent student with an ID in Special Primary Schools (SPS) Children 1 Padang.    Subjects and Method: This is a pre-experimental design with one group pretest-posttest design conducted from April to August 2022. The target population is all students with ID in SPS 1 Padang. This study used purposive sampling, and the sample size is 21. The independent variable of this study was sexual education using the Pop-up Book while the dependent variable was knowledge and attitude were measured using a questionnaire. Data were analyzed by paired t-test. Results: The average knowledge score increased after (Mean= 11.1; SD= 2.47) given the sexual education intervention with Pop-up book media compared to before (Mean= 9.33; SD=2.13), and this result was statistically significant (p = 0.028). The average attitude score increased after (Mean= 5.86; SD= 1.24) given the sexual education intervention with Pop-up book media compared to before (Mean= 3.67; SD= 0.48), and this result was statistically significant (p<o.001). Conclusion: The pop-up book efficacy for students’ understanding of sexual education. Keywords: teenager, perspective, mental retardation, recognition, pop-up book, sexual education. Correspondence: Arif Rohman Mansur. Department of Children and Maternity, Faculty of Nursing, Universitas Andalas, Padang West Sumatera, Indonesia. Email: arifrohmanmansurphd@nrs.unand.ac.id. Mobile: 085228892075.